2015
DOI: 10.1016/j.eururo.2015.03.037
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role of Transient Receptor Potential M8 (TRPM8) in a Model of Acute Cold-induced Urinary Urgency

Abstract: Brief cold stimuli applied to the skin can evoke a sudden desire to urinate, which can be highly bothersome in patients with overactive bladder. We developed an animal model to study this phenomenon, and found that it depends on a specific molecular cold sensor, transient receptor potential M8 (TRPM8). Pharmacological inhibition of TRPM8 may alleviate acute cold-induced urinary urgency in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 39 publications
(55 reference statements)
1
50
0
Order By: Relevance
“…It is proposed that imbalances of sensory functions within the urothelium and the suburothelial space, along with potential abnormalities of central function in processing of afferent signals, significantly contribute to the generation of storage lower urinary tract symptoms (Roosen et al, 2009). Advances in the understanding of TRPs in bladder sensing suggest that TRPM8 has important functions in bladder physiology and pathophysiology and that this receptor may be an emerging drug target in lower urinary tract symptoms (Franken et al, 2014;Uvin et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is proposed that imbalances of sensory functions within the urothelium and the suburothelial space, along with potential abnormalities of central function in processing of afferent signals, significantly contribute to the generation of storage lower urinary tract symptoms (Roosen et al, 2009). Advances in the understanding of TRPs in bladder sensing suggest that TRPM8 has important functions in bladder physiology and pathophysiology and that this receptor may be an emerging drug target in lower urinary tract symptoms (Franken et al, 2014;Uvin et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The bladder can react to thermal cold by at least two principally different neurophysiological doctrines: 1) by local activation of thermal receptors within its sphere, such as during the controversial ice-water test, which elicits a visceral sensorimotor reflex (the bladder-cooling reflex) (Hellström et al, 1991;Drake et al, 2010;Franken et al, 2014); or 2) by activation of somatosensory pathways, which is suggested to depend on segmental dichotomizing afferent axons of the skin and viscera (Shibata et al, 2011). However, the latter mechanism does not explain the occurrence of detrusor instability in response to everyday nonsegmental stimuli (e.g., hand-washing or cold weather urgency, or bladder contractions induced by cold exposure of cranial skin in rodents) (Choe et al, 1999;Ghei and Malone-Lee, 2005;Uvin et al, 2015). Less well understood processes or hypotheses such as plasticity in bladder sensory pathways (Chai et al, 1998), central nervous modulation of homeostatic afferent networks , or convergence of central nervous organization of somatosensory and central micturition pathways (Hedlund, 2015) have been suggested to construe acute coldinduced urgency (Uvin et al, 2015).…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations